The Relationship Between Menstrual Duration And Anemia Incidence In Adolescent Females at State Senior High School 7 Pekanbaru - Siti Qomariah; Ernita Laowo; Yusmaharani (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
Anemia is a health problem characterized by a decrease in hemoglobin levels below normal limits. In women, the normal hemoglobin level is 12–15 grams per deciliter. Several factors contribute to anemia in adolescent girls, including the menstrual cycle. According to the World Health Organization (WHO, 2023), the prevalence of anemia in adolescent girls is 30%. Anemia in adolescent girls can also have an impact on themselves, such as disrupting growth and development. This study aims to determine the relationship between menstrual duration and the incidence of anemia in female students at SMA Negeri 7 Pekanbaru. The research design used in this study is a quantitative study with an analytical observational design using a cross-sectional approach. The research was conducted at SMA Negeri 7 Pekanbaru on June 5, 2025. The instrument used in this study was a questionnaire and a hemoglobin measuring tool. The population in this study consisted of all 11th-grade female students at SMA Negeri 7 Pekanbaru, totaling 174 students. The sampling technique used was purposive sampling followed by systematic random sampling, with a total of 119 respondents. The data were analyzed using univariate and bivariate analysis with the chi-square test. The chi-square test results in this study showed a pvalue of 0.000 (p < 0.005), indicating that there is a significant relationship between menstrual duration and the incidence of anemia in adolescent girls. There is a relationship between menstrual duration and the incidence of anemia among female students at SMA Negeri 7 Pekanbaru. It is hoped that schools and healthcare personnel can collaborate in monitoring anemia rates to prevent anemia-related issues among adolescent girls.